Experimental characterization and modeling of the contact resistance of Cu-Cu bonded interconnects - Made, Riko I. (2012)
The effects of the surface roughness and applied loads on the specific electrical contact resistance of three-dimensional Cu–Cu bonded interconnects have been quantitatively investigated. Wafer-level thermocompression bonding was carried out on bonded Cu layers with either different surface roughness at a certain load or with similar surface roughness at different applied loads. Experimental results show that as the surface roughness of the Cu bonding layer increases or as the bonding load decreases, the specific contact resistance of the bonded interconnects increases. A model is presented which quantifies the relationship between the specific contact resistance and the true contact area (which is a function of the surface roughness and applied load). Through the true contact area, the integrity of a bonded interface may be predicted from the electrical measurement of the contact resistance.